Aerobic biodegradation potential of subsurface microorganisms from a jet fuel-contaminated aquifer. - Aelion, C M (1991)
In 1975, a leak of 83,000 gallons (314,189 liters) of jet fuel (JP-4) contaminated a shallow water-table aquifer near North Charleston, S.C. Laboratory experiments were conducted with contaminated sediments to assess the aerobic biodegradation potential of the in situ microbial community. Sediments were incubated with 14C-labeled organic compounds, and the evolution of 14CO2 was measured over time. Gas chromatographic analyses were used to monitor CO2 production and O2 consumption under aerobic conditions. Results indicated that the microbes from contaminated sediments remained active despite the potentially toxic effects of JP-4. 14CO2 was measured from [14C]glucose respiration in unamended and nitrate-amended samples after 1 day of incubation. Total [14C]glucose metabolism was greater in 1 mM nitrate-amended than in unamended samples because of increased cellular incorporation of 14C label. [14C]benzene and [14C]toluene were not significantly respired after 3 months of incubation. With the addition of 1 mM NO3, CO2 production measured by gas chromatographic analysis increased linearly during 2 months of incubation at a rate of 0.099 mumol g-1 (dry weight) day-1 while oxygen concentration decreased at a rate of 0.124 mumol g-1 (dry weight) day-1. With no added nitrate, CO2 production was not different from that in metabolically inhibited control vials. From the examination of selected components of JP-4, the n-alkane hexane appeared to be degraded as opposed to the branched alkanes of similar molecular weight. The results suggest that the in situ microbial community is active despite the JP-4 jet fuel contamination and that biodegradation may be compound specific.(ABSTRACT TRUNCATED AT 250 WORDS)